Selenium vacancies enriched the performance of supercapacitors with excellent cycling stability via a simple chemical bath deposition method. Issue 23 (16th May 2019) - Chebrolu, Venkata Thulasi-Varma; Balakrishnan, Balamuralitharan; Cho, Inho; Bak, Jin-Soo; Kim, Hee-Je
Abstract : Herein, we report a simple and cost-effective route for the fabrication of NiWO4, NiWO4 P, and NiWO4 Se nanostructures using the chemical bath deposition method. Abstract : Herein, we report a simple and cost-effective route for the fabrication of NiWO4, NiWO4 P, and NiWO4 Se nanostructures using the chemical bath deposition method. As a binder-free electrode material for pseudo capacitors (PCs), the fabricated nickel foam-supported NiWO4 Se exhibited an excellent cycling life of 3000 cycles with a high specific capacitance of 1115.05 F g −1 at 20 mA cm −2 . The desirable electrochemical performance of NiWO4 Se was mainly attributed to the large specific area, short ion diffusion distance, and the introduction of selenium, which provide transport pathways for electrons and provide more active sites for electrochemical energy storage. The present simple and scalable synthesis shows great potential for the future development of transition metal selenides for different energy storage and conversion applications.